Factors Affecting Student Achievement in Faculty of Economics "X" University - Lily Suhaily; Yasintha Soelasih (The Winners, 2015)
Education is an important point for many countries, including Indonesia. People with high education in a country could make the country wealthier. Parents are usually aware that it is important for their children to be educated. If the children are well educated, they will increase the standard of living of their parents and their selves. Based on this phenomenon, research evaluated factors that influence student achievement and also evaluated the difference of achievement between students who are active in campus activities and are not active. A number of 329 questionnaires were distributed to Faculty of Economics, “X” University students using random sampling. The result shows that the students themselves as factor that could determine their achievement. The evaluation also found that the achievement of student who is active in campus activities is different with the achievement of student who is not active in campus activities.